Konsep Taubat Menurut Imam Al-Ghazali - Rusydi Rusydi (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2023)
Abstract: The Concept of Repentance According to Imam Al-Ghazali. Humans are inseparable from a mistake that becomes sin, from small and big sins, sins that are willful and unintentional, sins that are born and are inwardly, and sins that are visible and invisible. Therefore, we as humans who are given reason to think and awareness become a desire to return to be close to the Creator. In life in this impermanent world, we often do things that violate the rules of Allah SWT in terms of its prohibitions. In which all of His prohibitions are things that are temporary enjoyment that ultimately cause misery or accidents for the doer. Nobody in this world wants an accident on him, in general they want good safety when they are in a world that wants an accident on him. In general, they want salvation both when they are in this world and in the hereafter. The problem in this research is what is the opinion of Imam al-Ghazali regarding the concept of repentance? The purpose of this research is to explain how the concept of repentance according to Imam al-Ghazali. This research uses library research method. For that in data collection the author uses the documentation method. Meanwhile, in the data analysis method, the researcher conducted a content analysis to explore the authenticity of the text and then descriptive analysis to describe the condition of the research subject based on facts. The conclusion in this study is that repentance according to Imam al-Ghazali is an effort of some heart work. In short, according to the scholars, repentance is to cleanse the heart from sins. Imam al-Ghazali emphasized that worshipers are required to repent for two reasons: First, in order to succeed in obtaining help in order to achieve obedience, because various acts of sin can give birth to bad luck and result in misfortune for the perpetrator. In addition, sinful actions can also hinder our efforts to obey and serve Allah SWT. Keyword: Repentance and Al-Ghazali